Pain Control in Lower Abdominal Surgeries in Post-Operative Period; Comparison of Transversus Abdominis Plane Block Vs Infiltration of Wound with Bupivacaine - Saira Naseem, Tahir Mahmood Chaudhary, Abdul Bary, Tahir Nazeer, Muhammad Abdul Aziz, Riaz Hussain, Amna Tahir, M. Baqir Ali Khan, (Pakistan Journal of Medical & Health Sciences, 2022)
Introduction: Post-operative pain is very common problem for both patients and medical professionals. Different medicines and procedures are used to treat it. Aim: To compare the efficacy of transversus abdominis plane block (TAP) with local anaesthetic infiltration in surgical wound regarding post-operative pain management. Study Design: Randomized control trial. Material & Methods: 60 patients (30 in each group) undergoing for lower abdominal surgery were included and divided into two group A and B by using lottery method. In group A bilateral TAP block was applied with 20 ml of 0.25 % bupivacaine on each side. In the triangle of petit with 16 gage Tuohy’s needle. In group B 40 ml of 0.25 % bupivacaine was given in the margins of surgical incision with full aseptic technique at the end of procedures. . Result: The mean age of patient was 36.70 ± 8.55 year while mean age in group A was 36.50 ± 9.48 year and in group B it was 36.90 ± 7.67 year. The mean pain in group A was 2.77 ± 2.21 and in group B it was 6.72 ± 1.00 The mean pain was statistically less in group A as compared to group B and P value was ≤ 0.05. Conclusion: Post-operative pain control was batter with TAP block as compare to incisional wound infiltration of local anaesthetic agent.